Self-management of Chinese University students' excessive smartphone use - Monica E Carr; Noah D Barsky (Faculty of Psychology, Universitas Negeri Yogyakarta, 2026)
This study investigated whether self-management can successfully reduce excessive smartphone use to improve quality of life. Two experimental conditions were examined: experiment 1 involved self-management components, and experiment two added a goal-setting component to the self-management intervention. Three Chinese university students aimed to develop self-control of their excessive smartphone use by identifying competing behaviors to reduce their phone usage, improve their sleep behaviors, and overall quality of life. A multiple baseline design with repetition across participants was adopted. Treatment effect scores were calculated using Non-Overlap of All Pairs (NAP). Results indicated that the self- management intervention achieved moderate effects, and the additional of a goal- setting component achieved strong treatment effects, for participants who successfully reduced their excessive smartphone use. This study contributes to the literature on the use of self-management to reduce excessive smartphone use amongst Chinese university students. It also contributes to the literature on the relevance and effectiveness of Applied Behavior Analysis (ABA) interventions in China.